Biosolids treatment and management processes for beneficial use - Girovich, Mark J. (Environmental science and pollution control series, 1996)
Details the economic, regulatory and environmental protection issues related to biosolids management and use. This work evaluates treatment technologies and management strategies for the beneficial utilization of municipal wastewater residuals. It presents cost information regarding the relative economic merits of reuse and disposal methods.